Factors Affecting Consumer Behavior Toward Purchasing Motor Insurance Policy in the Case of Selected Insurance Companies in Ethiopia - Habtamu Alebachew Legass; Aragaw Seid (Yayasan Adra Karima Hubbi, 2024)
This study examines the factors influencing consumer behavior in motor insurance policy purchases. It investigates the impact of demographic, cultural, social, economic, marketing, and psychological factors on consumer behavior. The research follows a quantitative approach, employing an explanatory and descriptive research design. Convenience sampling was used to select 384 respondents from a pool of 9,657 motor insurance policy users in Dessie Town, specifically from Awash, Global, Nib, and Nyala Insurance Companies. Data was collected through a questionnaire and analyzed using descriptive statistics and inferential analysis techniques such as t-tests, correlation, multiple linear regression, and one-way ANOVA. After the data collection, coding, recording, and analysis via SSPS 23 software. The findings indicate that demographic factors like age, gender, education, and religion do not significantly influence consumer behavior in purchasing motor insurance policies, except for income. However, variables such as attitude, awareness, perceived risk, and premium demonstrate a moderate relationship with consumer behavior. Regression analysis reveals that, except for attitude, the independent variables of awareness, perceived risk, and premium positively and significantly impact consumer behavior in motor insurance policy purchases.